Game strategies for business integration in the digital economy - Popkova, Elena G. (Advances in business marketing & purchasing ;, 2023)
Through the comprehensive consideration of alternative strategies and their highly accurate comparison from the perspective of quantitative characteristics, the game approach refines logic and increases the efficiency and expediency of making decisions on business integration. Game Strategies for Business Integration in the Digital Economy reveals the essence, features and benefits of various strategies for business integration in the digital economy. Presenting a general scientific idea of business integration from the perspective of the Game Theory, Game Strategies for Business Integration in the Digital Economy considers these game strategies for business integration in the digital economy: cluster strategy; public-private partnership; cooperation of universities and business entities; parks and innovation networks; the M&A strategy; foreign direct investment; the strategy for export development of international business integration. Advances in Business Marketing and Purchasing (ABM&P), offers leading edge theory, empirical research and practice on sensemaking, planning, implementing and evaluating of strategies in business-to-business marketing and purchasing.